Antituberculosis agent diaportheone B: synthesis, absolute configuration assignment, and anti-TB activity of its analogues - Swaroop, Pandrangi Siva; Raut, Gajanan N.; Gonnade, Rajesh G.; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2012)
First synthesis of diaportheone B, an antituberculosis agent isolated from endophytic fungus Diaporthe sp. P133 is reported using two complementary routes, a one step and a three-step sequence. The absolute configuration of diaportheone B was determined by using X-ray crystal structure analysis of its dibromo derivative. In addition, we have prepared several close analogues of diaportheone B and determined their anti-TB potential using Alamar-blue assay (H(37)Rv).